Internalisasi nilai-nilai pancasila sebagai landasan pembentukan keseimbangan psikologis dalam keluarga Indonesia - safi'i putra, dewangga islami (Maliki Interdisciplinary Journal, 2025)
The family is the first environment that plays an important role in shaping individual character, morality, and psychological balance. In the Indonesian context, Pancasila values serve as ethical guidelines that support family harmony and psychological well-being. This study analyzes the internalization of Pancasila values in Indonesian families and examines their contribution to the formation of psychological balance. Using a literature review method, this article explores scholarly journals, academic books, and publications related to value education and family psychological dynamics. The findings show that value internalization occurs through role modeling, habituation, moral communication, and contextualized application of values in daily activities. Pancasila values promote inner peace, relational warmth, emotional regulation, and a sense of fairness within families. These results highlight the importance of strengthening value education to build adaptive, moral individuals with stable psychological balance.